Ancistrocerus waldenii waldenii (Viereck 1906) (Hymenoptera: Vespidae, Eumeninae), a new addition to the fauna of Greenland - Wahlberg, Emma; Baião, Guilherme C.; Häggqvist, Sibylle; Martinsson, Svante; Pistone, Dario; Pape, Thomas (Zootaxa, 2014)
Ancistrocerus waldenii waldenii (Viereck 1906) is newly recorded from West Greenland. This is a new northern limit for the species.